1995
DOI: 10.1007/bf00854967
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the electromyographic spectrum power distribution caused by a progressive increase in the force level

Abstract: The purpose of the present study was to determine the specific changes occurring in the power spectrum with an increasing force level during isometric contractions. Surface electromyographic signals of the triceps brachii (TB) and the anconeus (AN) of 29 normal subjects were recorded during isometric ramp contractions performed from 0 to 100% of the maximum voluntary contraction (MVC) in a 5-s period. Power spectra were obtained at 10, 20, 30, 40, 50, 60, 70, 80 and 90% MVC. Changes in the shape of these spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…A similar tendency could be seen for the C11 parameter which also defines the band of high frequencies (~270-500 Hz) in the EMG power spectrum. These relationships are consistent with Bilodeau, Cincera, Gervais, et al's [27] conclusions, who reported that for the triceps brachii muscle there was a decrease in the power spectrum at high frequencies together ED S16 S13-S16 -PL S15, S16 S4, S15, S16 -…”
Section: Influence Of Force Level On Parameters Of Power Spectrumsupporting
confidence: 91%
“…A similar tendency could be seen for the C11 parameter which also defines the band of high frequencies (~270-500 Hz) in the EMG power spectrum. These relationships are consistent with Bilodeau, Cincera, Gervais, et al's [27] conclusions, who reported that for the triceps brachii muscle there was a decrease in the power spectrum at high frequencies together ED S16 S13-S16 -PL S15, S16 S4, S15, S16 -…”
Section: Influence Of Force Level On Parameters Of Power Spectrumsupporting
confidence: 91%
“…In the absence of significant muscle fatigue developing during each contraction, the present analysis of EMG activity reflects the relative activation of the muscle; therefore, any genderspecific pattern in torque production would mani- fest a similar response in EMG activity. Although gender differences in EMG signal (frequency content) have been observed previously, 4,6,37,39 the dynamic nature of the contractions in the present study would have likely yielded nonstationary signals, 47 confounding traditional frequency spectrum analyses.…”
Section: Discussionmentioning
confidence: 71%
“…As mentioned, the scientific literature has revealed some inconsistent findings regarding the effects of the level of intensity of contraction on the f med of the EMG. Some investigations have shown a negligible effect of the level of muscle force on the EMG f med for the triceps brachii (Bilodeau et al 1995), biceps brachii (Hagberg and Ericson 1982), muscles of the forearm (Petrofsky and Lind 1980), and the VM and RF muscles (Pincivero et al 2001). It appears, however, that certain muscles generate spectrum parameters of the EMG (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…The f med refers to the frequency in the sampled EMG bandwidth that divides the power spectrum into halves (Bilodeau et al 1995), and is considered to reflect the conduction velocity of the action potential of the muscle fiber (Kupa et al 1995). As mentioned, the scientific literature has revealed some inconsistent findings regarding the effects of the level of intensity of contraction on the f med of the EMG.…”
Section: Introductionmentioning
confidence: 98%